Effect of stobadine on gastric mucosal injury after ischaemia/reperfusion - Mojzis, J; Pomfy, M; Kohút, A; Benes, L; Nicák, A; Mirossay, L (Physiological research, 1996)
The ability of stobadine to prevent gastric mucosal injury was tested in rat gastric ischaemia induced by 30 min clamping of the coeliac artery with subsequent 30 min reperfusion. Serious injury of gastric mucosa (macroscopic and microscopic) and the increase of microvascular permeability was found after ischaemia/reperfusion in rats without stobadine. After oral pretreatment with stobadine (5 mg.kg-1, 30 min before surgery), the development of gastric mucosal lesions and changes of vascular permeability were significantly decreased.
Keywords: krysa rodu Rattus; mužské pohlaví; Regional Blood Flow; Male; žaludeční vředy; regionální krevní průtok; Reperfusion Injury; Gastric Mucosa; žaludeční sliznice; reperfuzní poškození; Rats; potkani Wistar; Ischemia; Animals; protivředové látky; ischemie; zvířata; kapilární permeabilita; Stomach Ulcer; Anti-Ulcer Agents; Rats, Wistar; Capillary Permeability; Carbolines; karboliny